Improving Foreign Investment Insurance in Uzbekistan (Eurasian Scientific Herald, 2023)
The theoretical and methodological basis of foreign investment insurance in Uzbekistan, the practice of foreign investment insurance, the existing problems in this field, analytical data have been explored in this article, also paper includes conclusions, suggestions and recommendations for improving foreign investment insurance.